2003
DOI: 10.1038/sj.onc.1206222
|View full text |Cite
|
Sign up to set email alerts
|

EGR2 induces apoptosis in various cancer cell lines by direct transactivation of BNIP3L and BAK

Abstract: EGR2 plays a key role in the PTEN-induced apoptotic pathway. Using adenovirus-mediated gene transfer to 39 cancer cell lines, we found that EGR2 could induce apoptosis in a large proportion of these lines by altering the permeability of mitochondrial membranes, releasing cytochrome c and activating caspase-3, -8, and -9. Analysis by cDNA microarray and subsequent functional studies revealed that EGR2 directly transactivates expression of BNIP3L and BAK. Our results helped to clarify the molecular mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 30 publications
1
75
1
Order By: Relevance
“…Two of the IRF-3-dependent genes are known transcription factors that stimulate apoptosis or growth suppression, Zac1 and Egr2/Knox-20. 38,39 In addition, there is an increase in expression of the Fas death domain-associated protein, Daax and a decrease in cyclin A1. Conversely, there is an apparent counterbalance to the promotion of apoptosis with the altered expression of genes that stimulate cellular proliferation.…”
Section: Irf-3 Target Genesmentioning
confidence: 99%
“…Two of the IRF-3-dependent genes are known transcription factors that stimulate apoptosis or growth suppression, Zac1 and Egr2/Knox-20. 38,39 In addition, there is an increase in expression of the Fas death domain-associated protein, Daax and a decrease in cyclin A1. Conversely, there is an apparent counterbalance to the promotion of apoptosis with the altered expression of genes that stimulate cellular proliferation.…”
Section: Irf-3 Target Genesmentioning
confidence: 99%
“…Functional annotation clustering using DAVID software (12) showed that 17 of the up-regulated genes function as activators of apoptosis (Table S2). It has been shown that these genes induce growth arrest and apoptosis in cancer cells (13)(14)(15). Using AnnexinV binding assays and flow cytometry analysis of DU145 cells transfected with GFP-tagged GFP-tagged C/EBPhomologous protein (CHOP), FBJ murine osteosarcoma viral (v-fos) oncogene homolog (FOS) and nuclear receptor subfamily 4, group A, member 2 (NR4A2), we confirmed that overexpression of these proteins induced apoptosis in DU145 cells, whereas GFP alone did not affect cell survival ( Fig.…”
Section: St3-h2a2mentioning
confidence: 99%
“…In addition, 5-aza-2 0 -deoxycytidine (a DNA methylation inhibitor) and 4-phenylbutyric acid (a histone deacetylase inhibitor) restore the expression of the epigenetically silenced miR-512-5p in human gastric cancer cells in which miR-512-5p induces apoptosis by suppressing the antiapoptotic Mcl-1 expression (Saito et al, 2009). EGR2 is a tumorsuppressive transcription factor, whose activation induces apoptosis by direct transactivation of BNIP3L and Bak (Unoki and Nakamura, 2003). To this end, the oncogenic miR-150 has been shown to target EGR2 to promote gastric cancer growth (Wu et al, 2010b).…”
Section: Dysregulated Mirnas In Gastric Cancermentioning
confidence: 99%